Fiddler on the roof [videorecording (DVD)] - Jewison, Norman, 1926-; Topol, 1935-; Crane, Norma, 1931-1973; Frey, Leonard, 1938-1988; Stein, Joseph; Sholem Aleichem, 1859-1916; Sholem Aleichem, 1859-1916; Bock, Jerry (MGM Home Entertainment, 2007)
Tevye the milkman struggles to raise five daughters as observant Jews in the rapidly changing society of pre-revolutionary Ukraine.